THE ANALYSIS OF INDONESIAN LANGUAGE ERRORS IN THE FINAL PROJECT OF CIVIL ENGINEERING STUDENTS IN POLINES - Rio Devilito; Wahyuningsih, Sri; Wahyumi, Puji; Latif, Wildana; Suroso (JURNAL SKRIPTA, 2025)
The implementation of Indonesian writing rules in accordance with the guidelines and Ejaan Yang Disempurnakan (in Indonesian called EYD) in academic writing, it must be really done with full accountability. In academic writing, it must be done responsibly. This can be done through the application of Indonesian rules in writing final projects (TA) for students of the Civil Engineering Department of the Semarang State Polytechnic (Polines). The problem that often arises is that the writing produced by students does not meet linguistic standards which is reflected in various Indonesian language errors such as spelling and punctuation errors, diction errors, and unclear sentence structures, causing ambiguity. The purpose of this research is to identify and analyze various errors in Indonesian language in the writing of TA students of the Department of Civil Engineering in Polines. This research is a qualitative research with a comprehensive content analysis approach. Students as an academic generation and agents of change are expected to have sensitivity to various problems that are currently faced in academic writing, one of which is the problem of Indonesian language errors in TA writing. The results of this study are in the form of descriptions of various errors in Indonesian, such as spelling, diction, and sentence structure errors that are not correct in the writing of TA students of the Department of Civil Engineering in Polines.